Recording the record-keepers news archiving in mainstream print, television, and digital news organizations in the Philippines - Inguito, Rafaella Louisette P.; Lucañas, Bianca Ysabelle
Journalism’s continuous evolution has given rise to new forms of news materials—from newspapers to broadcast television news episodes and digital news articles. What remains constant, however, is its role as a public good. Such responsibility not only makes news production imperative for journalism but also extends to the preservation of news regardless of format. Thus, the practice of news archiving grows increasingly important. Guided by UNESCO's Journalism as a Public Good, Zelizer’s Journalism as Collective Memory, and McLuhan's Media Ecology Theory, the study conducted interviews and participant observation to look into the existence of news archiving practices across nine mainstream print, television, and digital news organizations in the Philippines. The findings reveal that although news archiving has long been practiced, it is not institutionalized. Access is also limited: print and digital news archives impose monetary restrictions, whereas television news archives remain private solely for the internal use of broadcast corporations. The practice is further marred by multiple challenges: degradation of news materials, failures in archiving technology, substandard, inadequate, and fragile storage, understaffing, and budget constraints. Overall, the news archives do exist, yet they fall short and severely contradict journalism’s function as a public good and as a keeper of society’s memory.